Dual-Activity ACC-deaminase Phosphate-solubilizing Pseudomonas Seed Inoculation Improves Mustard Performance under Phosphorus Deficiency Stress (Journal of Agriculture and Biology, 2025)
Phosphorus is a critical macronutrient often limiting crop productivity, particularly in soils with low phosphorus availability. This field study investigated the phosphorus (P) deficiency tolerance of mustard under seed inoculation with 1-aminocyclopropane-1-carboxylic acid (ACC)-deaminase and phosphate-solubilizing strains of Pseudomonas fluorescens. The experiment followed a two-factor randomized complete block split plot design with three replications: Factor A included two P doses (0 and 50 kg ha⁻¹), and Factor B comprised three seed treatments (uninoculated control, inoculation with ACC-deaminase-only P. fluorescens, and inoculation with dual-activity P. fluorescens possessing ACC-deaminase and P-solubilizing traits). The soil was alkaline clay, low in organic matter and Olsen-P. Phosphorus application significantly improved all mustard traits, while rhizobacterial strains significantly influenced all parameters except plant height and P concentration. Their interaction was significant only for number of pods, number of leaves, seed yield, and P concentration. Compared to control, P application enhanced plant height, stem diameter, branches, pods, leaves, leaf area, leaf weight, chlorophyll content, seed yield, and P concentration by 30–67%. Inoculation with P. fluorescens possessing only ACC-deaminase improved most traits by 17–40% and seed yield by 1.7%, though it slightly reduced P concentration. Dual-activity P. fluorescens improved growth traits by 33–63%, seed yield by 10%, and P concentration by 5%. Compared to single-activity inoculation, the dual-activity strain resulted in 1.2–6.0-fold increases in key traits, with lower P concentration increase (1.7-fold). Maximum interaction effects were observed in number of pods (3.5-fold), number of leaves (2.0-fold), seed yield (1.7-fold), and P concentration (1.7-fold). Overall, P. fluorescens strains with dual ACC-deaminase and P-solubilizing activity consistently outperformed single-activity strains and showed potential to enhance mustard growth and yield under both P-deficient and fertilized conditions. Future research may focus on multi-strain co-inoculation strategies and testing across diverse agroecological environments.